Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Produktivitas Kinerja Personel pada Staf Intelijen Mabes TNI - Arif Suryanto (Madani Connection, 2025)
This study aims to analyze the Implementation of Human Resource Management on personnel productivity at the TNI Headquarters Intelligence Staff and identify factors that influence personnel productivity at the TNI Headquarters Intelligence Staff. This study uses a qualitative approach with interview techniques, observations, and focus group discussions to gain a deeper understanding. The findings of this study indicate that in the implementation of Human Resource Management at the Intelligence Staff through several stages in accordance with the theory of HR Malayu S.P Hasibuan 2009, namely planning, recruitment, selection, orientation and placement, training and development, and determining salary levels. Factors that influence personnel performance at the TNI Headquarters Intelligence are Factors that can influence performance are facilities and infrastructure, communication systems and career development. In addition, leadership and work environment factors can also influence increasing work productivity. Then there are inhibiting factors including changes in work methods from conventional to the digital era which requires employees to utilize the latest technology including online applications.